Dual processes in fear and anxiety: no effects of cognitive load on the predictive value of implicit measures. Issue 5 (4th July 2021) - Van Bockstaele, Bram; Tibboel, Helen; Larsen, Helle; Wiers, Reinout W.; Bögels, Susan M.; Salemink, Elske
ABSTRACT: Dual process models posit that combinations of impulsive and reflective processes drive behaviour, and that the capacity to engage in effortful cognitive processing moderates the relation between measures of impulsive or reflective processes and actual behaviour. When cognitive resources are low, impulsive processes are more likely to drive behaviour, while when cognitive resources are high, reflective processes will drive behaviour. In our current study, we directly addressed this hypothesis by comparing the capacity of implicit and explicit measures to predict fear and anxiety, either with or without additional cognitive load. In Experiment 1 ( N = 83), only explicit measures of spider fear were predictive of spider avoidance, and manipulating cognitive load did not affect these relations. Experiment 2 ( N = 70) confirmed these findings, as the capacity of explicit and implicit measures to predict self-reported and physiological responses to a social stressor was not moderated by cognitive load. In two experiments, we thus found no empirical support for the central dual process model assumption that cognitive control moderates the predictive value of implicit and explicit measures. While implicit measures and dual process accounts may still be valuable, we show that results in this field are not necessarily replicable and inconsistent.